ICAO : a history of the International Civil Aviation Organization - MacKenzie, David Clark, 1953- (University of Toronto Press, 2010)
MacKenzie demonstrates that ICAO has assumed a leading role in the struggle to secure civil aviation against sabotage and hijacking, while providing a forum for international concerns and disputes.